The Influence of Leadership Style and Organizational Culture on Employee Performance with Motivation as an Intervening Variable at the Secretariat of the Regional People's Representative Council of Jambi Province - Fadhil Wildan, Rachmad; Syekh, Saiyid; Akbar, Ali (DINASTI RESEARCH, 2025)
This study aims to analyze the influence of Leadership Style and Organizational Culture on Employee Performance with Motivation as an Intervening Variable in the Secretariat of the Regional People's Representative Council of Jambi Province. The method used in this study is a descriptive, verification and quantitative method. The object of research in this study is the influence of Leadership Style and Organizational Culture on Employee Performance with Motivation as an Intervening Variable in the Secretariat of the Regional People's Representative Council of Jambi Province. Based on the approach, it can be seen that the number of samples is 66 people. This study uses SPSS 26.0 analysis tools. Based on the results of the analysis carried out, the results obtained are that Leadership Style has a significant and positive effect on motivation, organizational culture has a significant and positive effect on motivation, leadership style has a significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, Leadership Style has a positive and significant effect on employee performance through work motivation and Organizational culture has a significant and positive effect on employee performance through motivation in the Secretariat of the Regional People's Representative Council of Jambi Province.